2002
DOI: 10.1046/j.1365-2842.2003.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the possible mechanism of cervical lesion formation by occlusal force

Abstract: Recently, various authors have proposed the interesting idea that occlusal force may be a principal factor in cervical lesions of the tooth. It is speculated that the lateral force in non-ideal mastication causes the tooth to bend and that the resulting tensile stress damages the enamel surface. In this study, we carried out stress analysis on the upper central incisor and the lower first molar using the plastic-elastic deformation theory with two-dimensional finite element method (FEM). The essential feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
25

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 11 publications
4
61
0
25
Order By: Relevance
“…This results are similar with Tanaka et al 15) which they reported that when the force was oblique, plastic deformation of the lower first molar appeared at the enamel surface along the cervical region because of the tensile stress. Spears et al 40) showed that a vertical force loaded at one tip of the lingual cusp of the mandibular second premolar produces tensile stress at the lingual enamel on the cervical region.…”
Section: ⅳ Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This results are similar with Tanaka et al 15) which they reported that when the force was oblique, plastic deformation of the lower first molar appeared at the enamel surface along the cervical region because of the tensile stress. Spears et al 40) showed that a vertical force loaded at one tip of the lingual cusp of the mandibular second premolar produces tensile stress at the lingual enamel on the cervical region.…”
Section: ⅳ Discussionsupporting
confidence: 92%
“…Based upon these data, 170 N was assumed as the chewing force for premolars and 500 N was assumed as the heavy parafunctional load of bruxism and traumatic occlusion. In this study, a tooth model loaded by a point load of static 500 N was considered more representative of high-risk loading situation, in contrast to other FEA studies [11][12][13][14][15][16] . Load-I for buccal eccentric occlusion and Load-II for palatal eccentric occlusion were selected.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Borcic et al 20) and Ichim et al 18) also went on an experiment with 200 N of loading. Therefore, stress range of intraoral loading seems to be within the value of 170 -200 N. In this study, a tooth model loaded by a point load of static 200 N was considered more representative of normal chewing load situation, in contrast to other FE analysis studies 23,[33][34][35] . Previous studies [18][19][20] were based on applying load on buccal cusp.…”
Section: ⅳ Discussionmentioning
confidence: 99%